2022
DOI: 10.1111/his.14698
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal tubulopapillary neoplasm (ITPN) of the pancreas: a distinct entity among pancreatic tumors

Abstract: Intraductal tubulopapillary neoplasm (ITPN) of the pancreas: a distinct entity among pancreatic tumorsAims: Intraductal tubulopapillary neoplasm (ITPN) of the pancreas is a recently recognized pancreatic tumor entity. Here we aimed to determine the most important features with a systematic review coupled with an integrated statistical approach. Methods and results: PubMed, SCOPUS, and Embase were searched for studies reporting data on pancreatic ITPN. The clinicopathological, immunohistochemical, and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
(142 reference statements)
1
2
0
Order By: Relevance
“…The present study confirmed the genomic distinctiveness of ITPN by showing that typical PDAC drivers, including KRAS, TP53, SMAD4, and CDKN2A, are less frequently altered in this lesion in comparison with conventional PDAC. Alterations in PDAC drivers, at similar or lower frequency, have already been reported in previous studies of pancreatic ITPNs 38 . The relative paucity of PDAC alterations in this case series highlights the molecular differences with conventional PDAC, but it should be acknowledged that KRAS alterations are still present in a not-negligible subset of cases (4/16 cases in this series, 25%).…”
Section: Discussionsupporting
confidence: 80%
“…The present study confirmed the genomic distinctiveness of ITPN by showing that typical PDAC drivers, including KRAS, TP53, SMAD4, and CDKN2A, are less frequently altered in this lesion in comparison with conventional PDAC. Alterations in PDAC drivers, at similar or lower frequency, have already been reported in previous studies of pancreatic ITPNs 38 . The relative paucity of PDAC alterations in this case series highlights the molecular differences with conventional PDAC, but it should be acknowledged that KRAS alterations are still present in a not-negligible subset of cases (4/16 cases in this series, 25%).…”
Section: Discussionsupporting
confidence: 80%
“…ITPN is positive for the pancreatic duct differentiation markers CK7, CK19, MUC1, and MUC6 [ 7 , 8 , 15 ] but negative for CDX2, MUC2, and MUC5AC [ 7 ]. These negative IHC results demonstrated no gastroenteric differentiation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basturk et al and Paolino et al discovered that approximately 70% and 60% of ITPN cases were associated with invasive carcinoma, respectively [ 7 , 15 ]. Invasive foci have features comparable to PDAC; biopsy of the tumor cells, including invasive cells, may lead to a false diagnosis of PDAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The newest edition (the 5th in 2019) of the World Health Organization (WHO) Guidelines classified the intraductal precursors of adenocarcinoma as IPMNs and included the previously considered variants of IPMNs, i.e., intraductal oncocytic papillary neoplasms (IOPNs) and ITPNs, as distinct neoplasms [ 10 , 29 ]. The dysplasia of these lesions may be either of low grade or high grade, and they eventually progress to invasive carcinoma.…”
Section: Diagnosismentioning
confidence: 99%